EVALUASI KINERJA LALU LINTAS PEMBANGUNAN UNDERPASS CIBITUNG KABUPATEN BEKASI DENGAN MENGGUNAKAN APLIKASI VISSIM (Kawasan Pasar Induk dan Stasiun Cibitung Kabupaten Bekasi) - Kurniawan, Fahri; Munawar, Achmad; Rizka Fahmi Amrozi , Mukhammad (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2023)
Bekasi District is one of the areas of the national economy that has a significant influence on the industrial sector. A large number of generation and attraction areas occur in the Main Market and Cibitung Station areas. The main market is a generation and pull area for people from inside or outside Bekasi Regency, while the Cibitung Station area is a new zone that is the generation and pull area for Jabodetabek commuter trips. One of the improvement activities in Bekasi Regency is the construction of the Cibitung Underpass. This underpass is located on Jalan Bosih Raya as a solution to traffic congestion in the Cibitung Station area. The existence of this underpass should provide a solution to congestion in the Pasar Induk and Cibitung Station areas, but if seen at this time the traffic conditions in the Cibitung Main Market Area are still experiencing congestion. The method used in this research is to create a validated traffic network model with the help of Vissim software. The model is then used to determine the performance of traffic sections and intersections both in terms of current conditions and in terms of the handling process. the optimization of the intersections were calculated using the MKJI model. Traffic performance of road sections and intersections will be obtained from alternative treatments. The expected research result is to get the best alternative that is able to reduce the value of queues and delays in the study area.